EDUCAÇÃO INCLUSIVA NA EDUCAÇÃO SUPERIOR: as condições de acesso e permanência de discentes surdos ou com deficiência auditiva na Universidade Federal do Maranhão. - ARAUJO, Maria Aparecida de Almeida (2020)
People with disabilities have continuously fought for rights to exert their citizenships and, with this, they have been achieving a few victories including the implementation of public policies in the educational field. In this context, the Brazilian Federal Legislation has created mechanisms aiming at eliminating and/or minimizing their social, educational, and professional exclusion. Thus, the present study titled “Inclusive education in higher education: conditions of access and maintenance of deaf or hearing disabled students in the Federal University of Maranhão”, aims at knowing and describing the perceptions of deaf Ufma students in relation to the conditions of access and maintenance in higher education. Therefore, an exploratory and descriptive research, with a qualitative approach, was conducted in the Dom Delgado campus, São Luís/MA from August to October 2019. Eleven students from UFMA and registered in Letters with focus on the Brazilian Sign Language, Pedagogy, Psychology, Tourism, Odontology, Theatre and Mathematics participated in the study. Seven of them are deaf and four have hearing disabilities, and four are male and seven female between 19 and 43 years old. Data were collected with authorization from the CEP/Conep/Ufma under the process 3.408.877 from 06/24/2019 with the application semi-structured interviews. The script used contained 15 questions related to the entering and staying in higher education in the context of an Inclusive Education. Interviews were mediated by a Brazilian Sign Language interpreter and filmed with authorization from interviewees. The results correspond to the facts that most deaf and/or hearing disabled students have accessed Ufma by the quotas and/or spot reservations; chose the undergraduate course by personal and/or professional interest; feel good in higher education; is able to communicate with non-disabled hearing colleagues; can only communicate with professors with the mediation of a Brazilian Sign Language interpreter; knows their rights as a deaf and/or hearing disabled student in higher education; have not been receiving specialized educational treatment and the teaching-learning process has not been fulfilling their specific educational needs; need to improve their learning; the acquired knowledge will contribute to their insertion in the work market; most professors are not capacitated for the teaching-learning process of deaf and/or hearing disabled students; most methods employed in class do not fulfill the specific educational necessities of such students; Ufma needs a higher amount of qualifications in the context of an Inclusive Education who knows the Brazilian Sign Language, as well as more interpreters. professors and other professionals involved in the teaching-learning process with